$T$-radical and strongly $T$-radical supplemented modules - Koşar, B.; Nebiyev, C. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We define (strongly) t-radical supplemented modules and investigate some properties of these modules. These modules lie between strongly radical supplemented and strongly $\oplus$ -radical supplemented modules. We also study the relationship between these modules and present examples separating strongly $t$-radical supplemented modules, supplemented modules,and strongly $\oplus$-radical supplemented modules.